Analysis of behavioristic learning theory based on John 4:1-42 and its application in Christian religious education - Telaumbanua, Arozatulo (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
Behavioristic learning theory is often ignored in the learning process to form student behavior. This is caused by the cognitive target or academic value of a student expected by educators. In addition, the lack of stimulants (stimuli) from an educator in terms of conveying learning material and new things that are raised will affect a student's less-than-optimal response. To carry out this research, the researchers used library research methods. Literature research is research that analyzes literary sources which are then included in this study. The purpose of this research is to understand and apply behavioristic learning theory based on John 4:1-42 in Christian Religious Education. It can be argued that behavioristic learning theory based on John 4:1-42 consists of encouragement from the Lord Jesus Christ for the Samaritan woman so that the Samaritan woman's response is very positive and maximal which results in changes in her behavior and that of others. Through this research, it can contribute to improving new learning systems to achieve the learning objectives of Christian religious education in shaping the character of students so that learning can be more enjoyable.